Livelihood Assets and Their Influence on The Sheep Farmer Households Welfare (Case in the Aerocity Area, Kertajati District, Majalengka Regency) - Kuswaryan, Sondi; Sitompul, Abdullah Afif; Firmansyah, Cecep; Fitriani, Anita; Daud, Andre Rivianda (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Livelihood assets are basic capital that must be managed well to realize household welfare. Survey research to analyze accessible livelihood assets and their influence on the level of welfare of sheep farmer households has been conducted in Kertajati Village and Pasiripis Village which are villages affected by the construction of the West Java International Airport in the Aerocity Area, Kertajati District, Majalengka Regency, with a sample of 45 farmer households. Multiple linear regression analysis models were used to determine the influence of social capital (X1), physical capital (X2), human resource capital (X3), natural resource capital (X4), and financial capital (X5), on the level of welfare of sheep farmer households (Y). The results showed that access to livelihood assets of sheep farmer households reached an average index value of 0.468 and an average welfare index value of 1.47. The model of the influence of access to livelihood assets can be used to predict the level of welfare (F Test; p <0.05), with a coefficient of determination R2 of 0.668. The mastery of livelihood assets that significantly affect the welfare of sheep farmer households (p<0.05) is human resource capital and financial capital, while social capital, natural resource capital, and physical capital do not have a significant effect (p>0.05). Therefore, in an effort to improve the welfare of sheep farmer households, priority must be given to improving human resources accompanied by financial support.